As long as the lemon trees Grow - Zoulfa Katouh (London Bloomsbury, 2022)
Burning with the fires of hope and possibility, AS LONG AS THE LEMON TREES GROW will sweep you up and never let you go. Salama Kassab was a pharmacy student when the cries for freedom broke out in Syria. She still had her parents and her big brother; she still had her home. She was even supposed to be meeting a boy to talk about marriage. Now Salama volunteers at a hospital in Homs, helping the wounded who flood through the doors. She knows that she should be thinking about leaving, but who will help the people of her beloved country if she doesn't? With her heart so conflicted, her mind has conjured a vision to spur her to action. His name is Khawf, and he haunts her nights with hallucinations of everything she has lost. But even with Khawf pressing her to leave, when she crosses paths with Kenan, the boy she was supposed to meet on that fateful day, she starts to doubt her resolve in leaving home at all. Soon, Salama must learn to see the events around her for what they truly are$1 (Bnot a war, but a revolution$1 (Band decide how she, too, will cry for Syria$1 (Bs freedoms
Keywords: English Fiction; English Novel